Comparison of Conventional and IPM Cropping Systems: A Risk Efficiency Analysis. (31st August 2020) - Lavik, Ming Su; Lien, Gudbrand; Korsaeth, Audun; Hardaker, J. Brian
Abstract: To support decision-makers considering adopting integrated pest management (IPM) cropping in Norway, we used stochastic efficiency analysis to compare the risk efficiency of IPM cropping and conventional cropping, using data from a long-term field experiment in southeastern Norway, along with data on recent prices, costs, and subsidies. Initial results were not definitive, so we applied stochastic efficiency with respect to a function, limiting the assumed risk aversion of farmers to a plausible range. We found that, for farmers who are risk-indifferent to moderately (hardly) risk averse, the conventional system was, compared to IPM, less (equally) preferred.